Strategi Manajemen Konflik dalam Proses Adaptasi Santri Baru di Pondok Pesantren Ra’iyatul Husnan Wringin Bondowoso - Dina Salsabila; Fikri Firmansyah; Putri Aisyah; Siti Hawiwk; Sinta Bela; Mu’alimin Mu’alimin (Jurnal Budi Pekerti Agama Islam, 2025)
This research examines conflict management strategies in the adaptation process of new students at the Ra'iyatul Husnan Bondowoso Islamic Boarding School. As traditional Islamic educational institutions, Islamic boarding schools often face various adaptation challenges experienced by new students, such as homesickness, conflicts between individuals, pressure from busy routines, and unpleasant treatment from senior students. Using a qualitative descriptive approach, this research identified various obstacles to adaptation, including loss of items and difficulty adapting, as well as resolution strategies which included introduction to the Islamic boarding school environment, mentoring programs, and providing motivation. Research findings show that positive interactions between students and the humanist approach of Islamic boarding school administrators play an important role in helping new students adapt and minimize conflict, both internal and between individuals.